Tanggapan Siswa Dan Kepala Sekolah Terhadap Pelaksanaan Pembelajaran Pendidikan Jasmani Olahraga Dan Kesehatan Selama Covid-19 Di SMP Negeri 1 Kutacane Tahun 2020. - Afrizal Afrizal; Panderi Panderi (Keguruan, 2020)
The purpose of the research is to see how far the implementation of sports and health physical education (PJOK) during Covid-19 at SMP Negeri 1 Kutacane in 2020, this type of research uses descriptive methods and qualitative approaches with evaluation research types. The number of subjects was 25 people. The results of the study, even though in the conditions of the Covid-19 pandemic, the learning process at SMP Negeri 1 Kutacane was still carried out, even with the physical sports and health education learning method using online media, the material taught was in accordance with the Learning Process Plan (RPP). The participation of students in PJOK learning was very enthusiastic even in a pandemic condition where the learning process for Physical Education Sports and Health continued using video/power point tutorials. In addition, the process of assessing students in online learning is carried out well